Natural Killer Cells in Liver Disease - Male, Victoria; Stegmann, Kerstin A.; Easom, Nicholas J.; Maini, Mala K. (Seminars in Liver Disease, 2017)
Natural killer (NK) cells comprise one of the most abundant immune cell populations in human liver and the nature and functions of these cells have been a focus of recent interest. Here, we consider the possible roles of NK cells in diverse liver diseases, concentrating on data from patient studies. NK cells can be protective, killing virally infected and cancerous cells in the liver and limiting fibrosis by eliminating hepatic stellate cells. However, they can also be deleterious, contributing to pathology in viral hepatitis by killing hepatocytes and downregulating virus-specific T-cell responses. It has recently emerged that a large fraction of hepatic NK cells constitute a distinct liver-resident subset and we highlight the need to distinguish between circulating and liver-resident NK cells in future studies. There is also a need for further investigation into how NK cells are influenced by the liver microenvironment and what scope there is to harness their immunotherapeutic potential.
Keywords: NK cells; liver residence; fibrosis; viral hepatitis; alcoholic liver disease; non-alcoholic fatty liver disease; hepatocellular carcinoma; autoimmune; transplantation